The Response of the Muslim Community in Indonesia when Lockdown was Reimplemented - Koni, Agung Subayu; Muhammad, Danang Wahyu; Erawan, M. Aufar Saputra Pratama; Arkan, Muhammad Alif (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
Although studies on the impacts of the pandemic on religious communities continue to emerge globally, studies on the response of religious communities in Indonesia have not yet been explored. Previous studies in Indonesia tended to focus on the following themes: the response to religion and the state, the response to government policies, the government's to COVID-19, and the public's response to the level of anxiety about the risk COVID-19. This study combines qualitative interview data. The goal is to understand Muslim communities, and their leader responds when Indonesia re-imposes its lockdown policy (PPKM). The findings in this paper are that the response of the Muslim community in Indonesia to changes in worship procedures and the mass closure of mosques in almost every region in Indonesia must be reviewed.